Antibiotic Susceptibility Patterns and Prevalence of Streptococcus Agalactiae Rectovaginal Colonization Among Pregnant Women in Iran - Mina Dashtizade; Mohammad Reza Zolfaghari; Masoud Yousefi; Ali Nazari-Alam (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective Streptococcus agalactiae is an important pathogen in neonates and pregnant women. Neonatal invasive infections due to S. agalactiae are life-threatening and preventive strategies for this challenge of human have become a concern. The aim of the present study was to determine the prevalence of rectovaginal colonization, related risk factors and antibiotic resistance pattern of S. agalactiae among pregnant women in Iran. Methods The present study was performed on 240 pregnant women. Vaginal and rectal swabs were obtained from all of the women and then were transferred to the laboratory. The isolation and identification of S. agalactiae was performed by standard microbiological tests and polymerase chain reaction (PCR) assay. The antimicrobial susceptibility patterns of the isolates were determined by the Kirby-Bauer disk diffusion. Polymerase chain reaction was used to detect ermB and mefA genes in erythromycin-nonsusceptible isolates. Results Out of 240 pregnant women, 16 cases (6.7%) were colonized by S. agalactiae. There is no significant association between demographic-obstetric factors and maternal S. agalactiae colonization in the pregnant women. Linezolid, vancomycin and ampicillin were the most effective antibiotics against S. agalactiae. The ermB gene was present in 6 (35.29%) S. agalactiae isolates. However, the mefA gene was not detected in any of the isolates. Conclusion Given the relatively significant prevalence of S. agalactiae colonization in the pregnant women in the present study and the risk of serious neonatal infections, the screening of pregnant mothers for the bacteria seems necessary. Our findings highlight the importance of appropriate antibiotic prophylaxis during pregnancy for the prevention of early onset S. agalactiae-neonatal infection and comorbidity.